Centrifugal model tests on the structural response of the shield tunnel when constructing cross passages by mechanical methods. (October 2022) - Lu, Ping; Yuan, Dajun; Jin, Dalong; Luo, Weiping; Liu, Minggao
Highlights: Model shield tunnel considering segments and joints in centrifugal model tests. Constructing cross passages by mechanical methods on shield tunnels. Reaction loading modes: back-thrust mode, front-traction mode. Measuring dislocations between segments. Abstract: Mechanical methods to construct cross passages between shield tunnels have received growing attention and have been successfully applied in several projects. However, the structural response of the shield tunnels under the construction load when excavating cross passages by mechanical method remains unclear. Centrifugal model tests were conducted in this paper to investigate the mechanical characteristics of the mainline tunnel loaded by two different reaction modes, i.e., back-thrust mode and front-traction mode. The results show that (1) stress concentration occurs at the segments around the opening of cross passages due to the change of the structural type, which may exceed the strength limit of the concrete; (2) the stress concentration was aggravated by the back-thrust load while alleviated by the front-traction load; (3) the back-thrust loading mode intensifies the trend of the horizontal ellipse of the mainline tunnel which is more adverse for shield tunnels. Therefore, the front-traction reaction mode is better for structural stress and deformation when no other supplementary measures are taken.